Inflammation in HFpEF: Key or circumstantial?. (15th June 2015) - van Empel, Vanessa; Brunner-La Rocca, Hans-Peter
Abstract: Heart failure (HF) can be split into HF with reduced ejection fraction (HFrEF) and HF with preserved ejection fraction (HFpEF). Currently the pathophysiologic mechanisms involved in HFpEF remain largely unknown. The neurohumoral and sympathetic nervous systems seem not to play a crucial role in HFpEF, as treatments targeting these pathways do not show beneficial effects in HFpEF patients, in contrast to HFrEF patients. A better understanding of the pathophysiological processes involved in HFpEF is needed, as there is no proven treatment for this disease at the moment. Recent data have yielded growing attention to the role of inflammation in HFpEF. In this review we discuss increased inflammation in HFpEF as demonstrated in translational animal models and human studies. This review evaluates whether inflammation plays a key role in HFpEF or is just a by-product of various comorbidities. Additionally, we analyze the involvement of oxidative stress and endothelial dysfunction and lastly we outline potential therapeutic targets. Highlights: The pathophysiologic mechanisms involved in HFpEF remain a topic of discussion. Inflammation seems to be important in the etiology of HFpEF. Increased oxidative stress and endothelial dysfunction are important in HFpEF. Is inflammation the key pathway causing HFpEF or an innocent bystander and just a consequence of HFpEF?